2022
DOI: 10.1177/01939459221128125
|View full text |Cite
|
Sign up to set email alerts
|

Sickness Symptoms in Kidney Transplant Recipients: A Scoping Review

Abstract: Sickness symptoms (depressive symptoms, anxiety, and fatigue) are common among people with chronic illness, often presenting as a symptom cluster. Sickness symptoms persist in many patients with chronic kidney disease, even after kidney transplantation (KT); however, little is known about sickness symptom-induced burden in KT recipients. This scoping review synthesizes available evidence for sickness symptoms in KT recipients, including findings on symptom prevalence, predictors, outcomes, interrelationships, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 84 publications
(231 reference statements)
1
2
0
Order By: Relevance
“…26 Different kinds of symptom clusters or complications arising from multiple factors in patients undergoing kidney transplant which, if unresolved for a long period, will affect the patients’ medication adherence, readmission rates, and mental health. 9,27 The findings of this study are similar to those of previous studies which have qualitatively identified that when persons with kidney transplant face different symptom experiences after surgery; the new symptom patterns can lead to feelings of insecurity and even disrupt their daily lives. 28 This also suggests that clinical nurses should assist patients in recognizing relevant symptoms and complications and strengthen home health education on management of symptoms and complications so that patients can adopt the correct way of coping in the face of symptom clusters and complications and better adapt to post-operative changes in physiological functioning.…”
Section: Discussionsupporting
confidence: 88%
“…26 Different kinds of symptom clusters or complications arising from multiple factors in patients undergoing kidney transplant which, if unresolved for a long period, will affect the patients’ medication adherence, readmission rates, and mental health. 9,27 The findings of this study are similar to those of previous studies which have qualitatively identified that when persons with kidney transplant face different symptom experiences after surgery; the new symptom patterns can lead to feelings of insecurity and even disrupt their daily lives. 28 This also suggests that clinical nurses should assist patients in recognizing relevant symptoms and complications and strengthen home health education on management of symptoms and complications so that patients can adopt the correct way of coping in the face of symptom clusters and complications and better adapt to post-operative changes in physiological functioning.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have also confirmed that anxiety and depression are common symptoms after KT. 43 Cognitive and emotional factors can impact the sleep quality of KTRs, resulting in increased levels of fatigue. 44 This highlights the interconnectedness of psychological and physical symptoms, where mental health can have a significant impact on physical well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of KTRs have shown growing attention to associations among depressive symptoms, anxiety, and fatigue (Sung et al, 2023). For example, in a study that examined psychosocial predictors of fatigue in KTRs, psychological distress, as defined by composite scores for depression and anxiety, was significantly associated with fatigue severity, reflecting the co-occurring or "clustering" tendency of sickness symptoms (Sands et al, 2023).…”
Section: Introductionmentioning
confidence: 99%